P49 Toxic cardiomyopathy in a stable hiv patient with a history of amphetamine misuse-a case report. (18th May 2015) - Raha, Durba; Fernando, Imali
Abstract : Background/introduction: Amphetamine (AM) use is associated with HIV infection among MSM. There are various toxic effects of AM, cardiotoxicity being one of them. Aim(s)/objectives: To present a case of report of cardiomyopathy secondary to AM misuse in a patient with well-controlled HIV. Case report: A 51 year old HIV positive MSM was admitted to hospital with dyspnoea, orthopnoea and decreased exercise tolerance. He was HIV positive since 1990 and this is stable on ARVs. CD4 count pre-admission was 514 with undetectable viral load. He used 25–30 grams of AM per week over a period of 20 years and had multiple casual unprotected MSM partners. On admission, the patient was tachycardic and hypoxic. Chest X-Ray on admission showed cardiomegaly and bi-basal opacification. Echocardiogram demonstrated severe left and right ventricular dysfunction, at a level requiring cardiac transplant. ECG showed prolonged QT interval. The patient was diagnosed with toxic dilated cardiomyopathy secondary to long term AM abuse. UK guidelines for Heart transplantation in adults deem chronic viral infection and ongoing substance misuse as relative contraindications to transplant. He was consequently commenced on medication for cardiac failure and received benzodiazepine as inpatient for managing withdrawal symptoms. On discharge, psychiatry follow-up was organised for support to help reduction of AM. At follow up, the patient reported reduced AM use by quarter, but felt he could never abstain. Discussion/conclusion: AM related cardiac fatalities are caused by acute myocardial necrosis, ventricular rupture, cardiomyopathy or arrhythmia. Evidence is mostly derived from case-reports. Patients using AM should be fully counselled regarding possible toxic effects.